Valid Entropy-Enthalpy Compensation: Its True Physical-Chemical Meaning - Starikov, E.B. (Journal of Applied Solution Chemistry and Modeling, 2013)
The notion of entropy-enthalpy compensation (EEC) is well known and hotly debated up to now. Nevertheless, any valid EEC phenomenon ought to have in sooth a definite physical-chemical sense. The roots of the latter are discussed here in detail